Graduate Business Program Admission Criteria and Student Graduate Academic Performance - Lizares, Maria Regina Lucia M.; Rahnema, Leila; Rey, Mia Pang; Suan, Ivy D.; Bautista, Carlos C. (Philippine Management Review; Vol 24 (2017), 2017)
The study evaluated a graduate business program by examining the student’s graduate academic performance and its admission procedure using several econometric procedures. The study shows that successful student’s graduate academic performance in the University of the Philippines’ graduate business program, both the Master in Business Administration (MBA) and MS Finance (MSF) degrees, can be consistently explained by the student’s past undergraduate academic performance and the quantitative aptitude test score. Reading and logic aptitude test scores, the two other measures of individual ability, did not seem to have a bearing on the student’s graduate academic performance. Hence, it is possible that altering the relative weights of the three test scores may change the profile of successful applicants and, at the same time, improve the overall efficacy of the admission procedure.